2019
DOI: 10.1002/cb.1749
|View full text |Cite
|
Sign up to set email alerts
|

Donation to charity and purchase of cause‐related products: The influence of existential guilt and experience

Abstract: Charity donation is an important prosocial behaviour that is often generated/strengthened by emotional stimuli from advertising. A similar strategy is often used to trigger the purchase of cause‐related products. The two activities represent direct and indirect methods of financial support and are important topics for researchers and practitioners. Charity donation and purchase of cause‐related products are typically investigated on the basis of different theoretical backgrounds; therefore, they are almost nev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 45 publications
0
51
0
Order By: Relevance
“…Pro-social behavior is defined as the voluntary behavior intended to benefit others (Bierhoff, 2002). This can be direct or indirect in nature (Urbonavicius et al, 2019) and can be in the form of sustainability-related behaviors (Champniss et al, 2016), financial donations (O'Loughlin Banks and Raciti, 2018), blood donations (Pentecost et al, 2017) and purchasing cause-related products (Urbonavicius et al, 2019), amongst others.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Pro-social behavior is defined as the voluntary behavior intended to benefit others (Bierhoff, 2002). This can be direct or indirect in nature (Urbonavicius et al, 2019) and can be in the form of sustainability-related behaviors (Champniss et al, 2016), financial donations (O'Loughlin Banks and Raciti, 2018), blood donations (Pentecost et al, 2017) and purchasing cause-related products (Urbonavicius et al, 2019), amongst others.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Others may also engage in the behavior for public recognition (Paramita et al, 2020; Wallace et al, 2017). In particular, prior research has showed that emotions can significantly influence pro-social behaviors in differential manners (O'Loughlin Banks and Raciti, 2018; Cialdini and Kenrick, 1976; Pham and Septianto, 2019; Septianto, 2020; Urbonavicius et al, 2019). For example, while both fear and empathy influence donation behavior, empathy leads to larger dollar donations and fear leads to small and medium dollar donations (O'Loughlin Banks and Raciti, 2018).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Several research on donations in the non-profit sector found the personal empathy value significant (Basil et al, 2008 ; Bergh & Reinstein, 2020 ; Martinez-levy et al, 2017 ; Verhaert & Van den Poel, 2011 ). In this respect, the impact of empathy on charitable donation intention is fully mediated by guilt responses (Basil et al, 2008 ), and there is a considerable amount of literature on guilt to be another relating factor for an individual's intention to donate to charity (Basil et al, 2008 ; Brennan & Binney, 2010 ; Urbonavicius et al, 2019 ). Identifying individual victims is essential for empathy and willingness to favour those who are suffering (Bleiker et al, 2013 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, when a consumer buys one pair of TOMS shoes, the company gives away a free pair to a child in need. Despite the popularity of the two helping modes, no research has compared these two modes with the exception of a recent paper by Urbonavicius, Adomaviciute, Urbutyte, and Cherian (2019). Their study found that the emotion of guilt was impactful under either of the two helping modes.…”
Section: The Moderating Role Of Helping Modementioning
confidence: 99%